Enhancing Students' Conceptual Understanding and Motivation in Electricity Through Web-Based Problem-Solving with PhET Simulations - Lubis, Patricia Hotma Minar; Lefudin, Lefudin; Khaokhajorn, Wacharaporn; Emiliannur, Emiliannur; Winarno, Nanang; Hakim, Lukman (FKIP Universitas Lampung, 2025)
This study explores the effectiveness of web-based problem-solving learning integrated with PhET simulations in enhancing students' conceptual understanding and motivation on the topic of electrical circuits. Utilizing a quasi-experimental method, the study involved 30 students from a private university in Palembang who engaged in web-based instruction supported by interactive simulations and contextual problem-solving activities. Data were collected through a learning style questionnaire, a concept understanding test, and a motivation questionnaire administered via Google Forms. The results revealed a significant increase in students' post-test scores across five indicators of conceptual understanding electric current, potential difference, resistance, Ohm's Law, and circuit configuration with N-Gain values ranging from moderate to high. Notably, students with auditory and kinesthetic learning styles showed slightly higher gains. Learning motivation also demonstrated a very high category, with 88% of students indicating strong interest and persistence in the learning process. The integration of web-based platforms and PhET simulations not only facilitated flexible and personalized learning experiences but also supported students' engagement, exploration, and self-regulation. These findings highlight the potential of technology-enhanced science instruction to bridge cognitive and affective learning domains, making it a valuable approach for future pedagogical innovations in physics education. Keywords: web-based learning, conceptual understanding, learning motivation.